2012
DOI: 10.1073/pnas.1117584109
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies and IL-3 support helminth-induced basophil expansion

Abstract: Basophils are powerful mediators of Th2 immunity and are present in increased numbers during allergic inflammation and helminth infection. Despite their ability to potentiate Th2 immunity the mechanisms regulating basophil development remain largely unknown. We have found a unique role for isotype-switched antibodies in promoting helminth-induced basophil production following infection of mice with Heligmosomoides polygyrus bakeri or Nippostrongylus brasiliensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
5
28
2
Order By: Relevance
“…This finding indicates that IgE mediates rapid worm expulsion and thereby limits the spread of the disease. FcRγ −/− mice were reported to lack basophilia in response to Hp infection, indicating that immune complexes act directly on basophils or their precursors to enhance proliferation and survival (18). However, our results challenge this concept, because we observed normal basophilia in FcRγ −/− mice, IgE ki/ki mice, and IgE −/− mice after Hp or Nb infection.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This finding indicates that IgE mediates rapid worm expulsion and thereby limits the spread of the disease. FcRγ −/− mice were reported to lack basophilia in response to Hp infection, indicating that immune complexes act directly on basophils or their precursors to enhance proliferation and survival (18). However, our results challenge this concept, because we observed normal basophilia in FcRγ −/− mice, IgE ki/ki mice, and IgE −/− mice after Hp or Nb infection.…”
Section: Discussioncontrasting
confidence: 56%
“…Basophil levels declined to basal levels 3 wk after infection in both KO and control mice, and we observed no differences during expansion after secondary infection. In contrast to a previous report (18), we also found unimpaired basophilia in FcRγ −/− mice (Fig. S5).…”
Section: Basophils Provide Early Il-4 For Th2 Polarization During Seccontrasting
confidence: 56%
See 1 more Smart Citation
“…A similar concept is illustrated by a requirement for antigen-independent tonic signals through the B-cell receptor for B-cell development (41)(42)(43). It has been suggested that isotype-switched antibodies and FcRγ expression play a role in supporting Heligmosomoides polygyrus-induced expansion of basophils (44). This and other studies suggest that expression of FcRγ plays an instrumental role in basophil responses (24), and here we suggest an additional role for FcRγ that is independent of antibody binding.…”
Section: Discussionmentioning
confidence: 99%
“…The striking role of the activating IgG receptor FcgRI (CD64) in larval immobilization by alternatively activated MF was unexpected due to the well-described involvement of this receptor in type 1 responses such as autoimmunity and protection against bacterial infection (35). Moreover, infection with the intestinal nematode H. polygyrus bakeri is associated with high levels of IgG1 in IS from challenge-infected or vaccinated mice, which has therefore been suggested to be the most relevant Ab isotype for protection (16,42,43). However, IgG1 or IgG1 immune complexes have been reported to bind to FcgRs II and III, but not FcgRI (30,44).…”
Section: Discussionmentioning
confidence: 99%